A Comparative Study on the Interaction of Sulfonamide and Nanosulfonamide with Human Serum Albumin - G. Rezaei Behbehani; Moayed Hossaini Sadr; H. Nabipur; L. Barzegar (Journal of Chemistry)
Binding parameters of the N-phenyl benzene sulfonyl hydrazide, sulfonamide, and nanosulfonamide interaction with human serum albumin were determined by calorimetry method. The obtained binding parameters indicated that sulfonamide in the second binding sites has higher affinity for binding than the first binding sites. The binding process of sulfonamide to HSA is both enthalpy and entropy driven. The associated equilibrium constants confirm that sulfonamide binds to HSA with high affinity (2.2×106 and 3.86105 M−1 for first and second sets of binding sites, resp.). The obtained results indicate that sulfonamide increases the HSA antioxidant property. Nanosulfonamide has much more affinity for HSA (3.6×106 M−1) than sulfonamide.